Уявлення про минуле як засіб самопрезентації українського дворянина другої чверті XIX ст. (за юнацьким щоденником Григорія Ґалаґана) - Будзар, М.М. (Сіверщина в історії України, 2020)
У статті досліджується проблема юнацького самовизначення представника української регіональної еліти – землевласника, громадського й культурно-освітнього діяча Григорія Ґалаґана. Як засіб такої самопрезентації розглянуто уявлення Г. Ґалаґана про минуле України, що відклалися у його особистому щоденнику, який він вів на порозі дорослішання – з 16 до 22 років. Метою статті є розгляд механізму формування історичного світосприймання Г. Ґалаґана як члена регіональної спільноти – дворянства Лівобережної України. Проблемний аналіз юнацького щоденника Г. Ґалаґана є інструментом для відтворення складного процесу оформлення історичних уявлень особи, котра постає перед одним з найважливіших викликів своє юності – вибором ідентичності. Відповідь на цей виклик дається, зокрема, й тим, як молода людина осмислює історію своєї батьківщини. In the article the problem of youthful self-determination of the representative of the Ukrainian regional elite – landowner, public and cultural and educational figure Hryhotii Galagan is researched. As a means of such self-presentation, was considered H. Galagan’s conceptions about Ukrainian history, which were put down in his personal diary, which he kept at the age of 16 to 22 years old. The Ukrainian nobleman appears in it as the «hero of his time» before the challenges of the «Nicholas era», that is the time of the reign of Nicholas I, when the Russian Empire was experiencing the apogee of absolutism, and at the same time the emergence of national movements, including the Ukrainian. He appears in different spaces of social action – in an aristocratic salon, in a university auditorium, in a landowner estate. The aim of the article is to analyze the formation mechanism of H. Galagan historical worldview as a member of the regional community – representative of the Left Bank Ukraine nobility. In this community, the modern national movement sprouted through its connection with the traditions of early-modern «Cossack Ukraine», through the formation of the «Cossack myth», through a rethinking of the folk culture traditions that has preserved the historical experience of the Ukrainian peasantry. The author used methods of archivistics – genetic and problem personalization, as well as methods of source analysis, first of all attribution and chronology of the source. The problem analysis of H. Galagan’s youth diary, first once fragmentary published at the end of the XIX-th century, is a tool for reproducing the complex process of designing the historical concepts of a person who faced before the most important challenges of his youth – the choice of identity. The answer to this challenge was given, in particular, by the way a young person interpreted the history of his Motherland.